Influence of Spirituality on Bitter Kola Consumption Among Pretoria Residents in Response to COVID-19 and Related Illnesses - Daniel Orogun; Harold G. Koenig (Religions)
The agrarian continent of Africa has many fruits with nutritional, medicinal and spiritual values. Regardless, Africa leads the statistics of poor healthcare globally. Two major challenges in Africa’s healthcare system are poor access and the high cost of medical healthcare. Among others, the effects of such challenges include low responsiveness to medical treatment and a high mortality rate. However, it seems the nosophobia that accompanied the global mortality rate during the COVID-19 pandemic may have triggered a spiritually influenced alternative. One of the traditional alternatives was a subscription to Garcinia Kola, popularly known as Bitter Kola (BK). This article, majoring in spiritual and not psychological influence, raised a hypothetical question: does spirituality influence Africans’ traditional response to COVID-19? To answer this question, Sunnyside in Pretoria was chosen as a demography to investigate the hypothesis. Data were collected via mixed research methods. There were 16 qualitative respondents, including sellers, herbalists and clergies, and 75 consumers as quantitative respondents under probability sampling. The results analysed using Excel and Python’s regression analysis demonstrated strong connections between consumers’ spiritual motivations, the sales period, the sales rate, and the swift traditional response to the pandemic and related illnesses. The outcome validated the influence of spirituality on 60.9% of quantitative respondents and showed how 25–72% responded to COVID-19 symptoms with BK. Likewise, 87.5% of qualitative respondents consumed BK via indigenous spiritual knowledge in response to the pandemic. Subsequently, this article discussed the benefits, limitations and lessons of spiritual influence on BK consumption in the post-COVID-19 era.